2021
DOI: 10.1590/1678-7757-2020-1058
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: emerging players in apical periodontitis

Abstract: Apical periodontitis is an inflammatory disorder of periradicular tissues developed from endodontic infections. Understanding its pathophysiology and the underlying molecular mechanisms is key to the advancement of endodontics. MicroRNAs (miRNAs), a group of evolutionarily conserved small non-coding RNAs, may be phenotypically and functionally associated with the pathogenesis of apical periodontitis. Several studies have focused on the role of miRNAs in the pulp and periradicular biology, and they have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Most importantly, miRNAs have been implicated as valid regulators that can modulate multiple biological processes, including bone regeneration and anti-inflammatory response (46, 47). As Shen and Silva (25) have reported that over 100 miRNAs were differentially expressed in AP and the highest expression of miR-10a-5p appeared to be involved in triggering anti-inflammatory signaling and promoting healing. It is noteworthy that different phases of inflammatory conditions may have different effects on the bone regenerative capacity of stem cells, as (48) showed that long-term exposure to pro-inflammatory cytokines inhibited the osteogenic differentiation of SCAPs.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Most importantly, miRNAs have been implicated as valid regulators that can modulate multiple biological processes, including bone regeneration and anti-inflammatory response (46, 47). As Shen and Silva (25) have reported that over 100 miRNAs were differentially expressed in AP and the highest expression of miR-10a-5p appeared to be involved in triggering anti-inflammatory signaling and promoting healing. It is noteworthy that different phases of inflammatory conditions may have different effects on the bone regenerative capacity of stem cells, as (48) showed that long-term exposure to pro-inflammatory cytokines inhibited the osteogenic differentiation of SCAPs.…”
Section: Discussionmentioning
confidence: 90%
“…Inflammation of periapical tissues commonly presents with the destruction of the alveolar bone, which is generally treated by controlling the infection and eliminating the inflammation to promote the repair of the periapical bone defects ( 40 43 ). Currently, miRNAs, transglutaminases, and other agents have been found to be involved in the development and progression of oral diseases ( 25 , 44 , 45 ). Most importantly, miRNAs have been implicated as valid regulators that can modulate multiple biological processes, including bone regeneration and anti-inflammatory response ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 presents the exemplary miRNA occurring within the periapical lesions on the basis of the literature [61,[68][69][70][71][72].…”
Section: The Role Of Microrna (Mirna) In Bone Resorption and Pathogenesis Of Apical Periodontitismentioning
confidence: 99%
“…), cytokines, chemokines, RANK/RANKL/OPG system and neuropeptides [ 2 , 7 ], which influence the balance between tissue destruction and regeneration in AP [ 7 ]. Innumerable investigations have been conducted to study the pathogenesis of AP and this dynamic shift; however, the exact etiological factors and the mechanisms associated with molecular changes has been not well elucidated [ 8 , 9 ]. What is the crucial factor in mediating this homeostasis in a periapical lesion?…”
Section: Introductionmentioning
confidence: 99%